Contribution of Plays and Toys to Children’s Value Education - ÖNDER, Mustafa (Asian Journal of Education and Training, 2018)
Plays and toys have an important place in the education of children. Children learn by seeing and doing rather than reading, listening and understanding. Play is an important “job” for children. The basic function of plays is to facilitate children’s adaptation to the world. Children can understand the real world by playing. They deal with unwanted situations by playing games. Moreover, they construct the building blocks of language and concept development through playing. They try different social roles by playing games. Again, through playing, they find the stimulants that are not readily available in real life. Children learn self-regulation, setting up rules and abiding by these rules through plays. They play to experience, understand and learn the things they cannot do in real life. For a child who ascribes a meaning to toys and objects, playing games and playing with toys is a serious business. Situations which are imaginary at first help children learn some rules, take a step beyond their development and construct their own zone of proximal development. All children have an imaginary friend when they are small. During this process which is a normal development pattern and a helpful occupation, the playmate is usually a toy. Playing games and playing with toys is not just an occupation, but also an activity that supports children’s mental health and helps them establish and develop emotional relationships. Plays and toys have a close relationship with education, history, geography, sociology, psychology, politics, industry and tourism, in short, with culture. Plays and toys are used as a method for early diagnosis of some disorders such as learning difficulty and autism. In these days where we seek solutions to digital addiction, plays and toys emerge as an important alternative. Plays also provide a suitable environment for value and morals education. Introducing plays and toys which have an important place in child education and using them more effectively in value and morals education together with other fields of development is of critical importance. In this theoretical article, we tried to address the importance of plays, toys and toy museums from this perspective.